Working Memory Training is Associated with Long Term Attainments in Math and Reading - Söderqvist, Stina; Bergman Nutley, Sissela (Frontiers in Psychology, 2015)
Training working memory (WM) using computerized programs has been shown to improve functions directly linked to WM such as following instructions and attention. These functions influence academic performance, which leads to the question of whether WM training can transfer to improved academic performance. We followed the academic performance of two age-matched groups during two years. As part of the curriculum in grade 4 (age 9-10), all students in one classroom (n = 20) completed Cogmed Working Memory Training (CWMT) whereas children in the other classroom (n = 22) received education as usual. Performance on nationally standardized tests in math and reading comprehension was used as outcome measures at baseline and two years later. At baseline both classes were normal/high performing according to national standards. At grade 6, reading comprehension had improved to a significantly greater extent for the training group compared to the control group (medium effect size, Cohen’s d = 0.66, p = 0.045). For math performance the same pattern was observed with a medium effect size (Cohen’s d = 0.58) reaching statistical trend levels (p = 0.091). Moreover, the academic attainments were found to correlate with the degree of improvements during training (p-values < 0.05). This is the first study of long-term (>1 year) effects of WM training on academic performance. We found performance on both reading and math to be positively impacted after completion of CWMT. Since there were no baseline differences between the groups, the results may reflect an influence on learning capacity, with improved WM leading to a boost in students’ capacity to learn. This study is also the first to investigate the effects of CWMT on academic performance in typical or high achieving students. The results suggest that WM training can help optimize the academic potential of high performers.